Subjective Expectations of Medical Expenditures and Insurance in Rural Ethiopia - Zelalem Yilma; Owen O'Donnell; Anagaw Mebratie; Getnet Alemu; Arjun S. Bedi (Tinbergen Institute, 2015)
Little is known about perceptions of medical expenditure risks despite their presumed relevance to health insurance demand. This paper reports on a unique elicitation of subjective probabilities of medical expenditures from rural Ethiopians who are offered the opportunity to purchase health insurance. We find that expectations are positively correlated with past expenses to a degree that exceeds the serial correlation in realized expenditures, suggesting overestimation of persistence and underestimation of the potential gains from insurance. Despite the fact that forecast expenditures do predict realized expenditures to some extent, there is no evidence that expectations influence the decision to take out health insurance, although plans to insure are positively related to the perceived dispersion of medical expenses.
Keywords: D82; D84; I13; O12; 330; Subjective probability; medical expenditure; out-of-pocket payments; adverse selection; health insurance; Ethiopia